Relevansi Informasi Akuntansi dan Struktur Kepemilikan Non Publik terhadap Keputusan Investasi - Riza Wisnu Prakasa; Pujiono Pujiono (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to evaluate the relevance of accounting information values, specifically Return on Assets (ROA), Earnings Per Share (EPS), and Non-Public Ownership (NPO), in investment decision-making. The research employs a quantitative method, utilizing a sample of 49 companies in the infrastructure, utilities, and transportation sector. Multiple linear regression analysis is applied to test the proposed hypotheses. The findings reveal that EPS and Non-Public Ownership significantly influence stock price movements, while ROA shows no significant effect on stock prices. The implications of this study highlight the importance of considering NPO and the relevance of accounting information values such as EPS, while also acknowledging the potential risks associated with ROA in the investment decision-making process.